A Comparison Learning TOEFL Experiences of English and Non-English Students - maharani, fitria erine; prasisca, dhea; karmida; lala, asmai (Indonesian Journal of ELT and Applied Linguistics, 2023)
This article was created to explain the results of learning experience of Indonesian English and Non-English students in TOEFL subject. The method used in this research was qualitative research method with a scientific approach. In this study, the Researcher used participants coming from different Universities in Indonesia, namely; Universitas Muslim Nusantara Al-Washliyah, Universitas Muhammadiyah Sumatera Utara, Universitas Islam Sumatera Utara, Universitas Islam Negeri Maulana Malik Ibrahim Malang. All the data were obtained through interviews which were categorized into thematic analysus. The results showed that TOEFL became a compulsory course that must be taken by English students and became a reference for getting a good job for non-English students. Artikel ini dibuat untuk menjelaskan hasil pengalaman belajar siswa Bahasa Inggris dan Non-Bahasa Indonesia pada mata pelajaran TOEFL. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan pendekatan saintifik. Dalam penelitian ini Peneliti menggunakan partisipan yang berasal dari berbagai Universitas di Indonesia yaitu; Universitas Muslim Nusantara Al-Washliyah, Universitas Muhammadiyah Sumatera Utara, Universitas Islam Sumatera Utara, Universitas Islam Negeri Maulana Malik Ibrahim Malang. Semua data diperoleh melalui wawancara yang dikategorikan ke dalam analisis tematik. Hasil penelitian menunjukkan bahwa TOEFL menjadi mata kuliah wajib yang harus diambil oleh pelajar bahasa Inggris dan menjadi acuan untuk mendapatkan pekerjaan yang baik bagi pelajar non-bahasa Inggris.